2022
DOI: 10.1021/acs.cgd.2c00145
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Single-Crystalline ZnO Films on 18%-Lattice-Mismatched Sapphire Substrates Using Buffer Layers with Three-Dimensional Islands

Abstract: Heteroepitaxial growth of single-crystalline zinc oxide (ZnO) films on a c-plane sapphire substrate is an important technology for electronics and optoelectronic devices. Recently, the inverted Stranski–Krastanov (SK) mode has been demonstrated, and it has realized the heteroepitaxial growth of ZnO films on a sapphire substrate by sputtering. In this mode, a 10 nm-thick buffer layer consisting of three-dimensional islands (3D buffer layers) initially forms and relaxes the strain, and then, a two-dimensional Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The immobilization of the ZnO nanostructures on suitable substrates also exhibit the emergence of new physical properties. For example, it has been observed that the heteroepitaxial growth of ZnO films on the c -plane of sapphire substrates leads to the observation of the inverted Stranski-Krastanov mode, which is of significance in elecronics and optoelectronics nanodevices . Therefore, it can be conceived that the variation in geometrical structures, exposed crystal facets, nature and concentration of the surface defects, possible charge separation, and orientation to hierarchical architectures can lead to tuning of the physicochemical characteristics.…”
Section: Crystallinity and Physical Propertiesmentioning
confidence: 99%
“…The immobilization of the ZnO nanostructures on suitable substrates also exhibit the emergence of new physical properties. For example, it has been observed that the heteroepitaxial growth of ZnO films on the c -plane of sapphire substrates leads to the observation of the inverted Stranski-Krastanov mode, which is of significance in elecronics and optoelectronics nanodevices . Therefore, it can be conceived that the variation in geometrical structures, exposed crystal facets, nature and concentration of the surface defects, possible charge separation, and orientation to hierarchical architectures can lead to tuning of the physicochemical characteristics.…”
Section: Crystallinity and Physical Propertiesmentioning
confidence: 99%